Fundamental research on the dynamic safety of a high-speed train under strong wind conditions. Issue 6 (3rd June 2023) - Liu, Dongrun; Liang, Xifeng; Zhou, Wei; Zhong, Mu; Lu, Zhaijun
Abstract : New engineering phenomena in China have renewed interest in research on the dynamic risk boundaries and characteristics of train overturning, derailment, and the interaction mechanism with aerodynamic loads in windy conditions. This study focuses on this challenge, the train aerodynamic loads characteristics, dynamic response and safety risk characteristics, and the contribution rate of different aerodynamic loads to train safety risks in different wind scenarios were investigated by computational fluid dynamics and multi-body dynamics simulation. The results reveal that when a train is completely exposed to strong winds with or without a windbreak, the safety risk assessment should focus on the overturning coefficient of the first wheelset of the first bogie of the head car. When the train is gradually exposed to strong winds, the probability of the train derailing risk is greatly increased. The train safety risk assessment should not only focus on the overturning coefficient, and more attention should be paid to the derailment coefficient of the first wheelset of the first bogie of the head car. In addition, there may be a risk of misjudgment in assessing the crosswind safety of trains from the aerodynamic point of view only by lateral force, lift force, and roll moment.